2003
DOI: 10.1097/00003072-200307000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Primary Chemotherapy Effect in Sentinel Node Detection in Breast Cancer

Abstract: Preoperative chemotherapy seems to impair axillary evaluation by SN biopsy and should be used cautiously in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Reports on the efficacy of SNB after pre-operative chemotherapy have been inconsistent [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], leading to suggestions that chemotherapy may interfere with the anatomy or physiology of the lymphatics and adversely affect its accuracy. In meta-analysis of SNB after pre-operative chemotherapy in patients with breast cancer, it shows that SNB is a reliable tool for planning treatment after pre-operative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the efficacy of SNB after pre-operative chemotherapy have been inconsistent [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], leading to suggestions that chemotherapy may interfere with the anatomy or physiology of the lymphatics and adversely affect its accuracy. In meta-analysis of SNB after pre-operative chemotherapy in patients with breast cancer, it shows that SNB is a reliable tool for planning treatment after pre-operative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another discussion is the elimination or not of SLN before neoadjuvant chemotherapy, because there may be a complete response with regression in the metastases of some lymph nodes, but the disease may remain in other ones (Noguchi et al, 2004). In contrast, Vigário et al (2003), reported that the accuracy of axillary staging after therapy is not well defined and may be associated with an increase of false negative results in these patients because chemotherapy may influence the standard drainage and, consequently, the responses of metastasis to therapy are different (Vigário et al, 2003). The absolute contraindications are: clinically positive axilla, core biopsy or fine needle aspiration biopsy with tumoral infiltration, allergy to vital blue dye and/or radiocolloid.…”
Section: Resultsmentioning
confidence: 99%
“…The relative contraindications are: previous biopsy or previous axillary surgery to remove some lymph nodes which occur during the procedure reflecting on the tumour's primary site; in these cases, lymphoscintigraphy has a fundamental role, in advanced stages, the tumour's size, multifocal and multicentric disease. Some authors report that age and body mass index also influence in the detection of SL because adipose tissue is supposed to reduce lymphatic fluid in such tissues (Vigário et al, 2003;Filippakis and Zografos, 2007). The aim of the detection of the SLN is to reduce postoperative morbidity resulting from axillary lymphadenectomy and maintain the correct staging of axilla in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T, tumor size; NAET, neoadjuvant endocrine therapy age patterns by shrinkage and fi brosis of the lymph vessels, inducing fatty degeneration associated with apoptosis of the tumor cells, and by the potential obstruction of lymphatic channels with cellular material or tumor emboli. [33][34][35] Second, the action of NAC on lymph nodes may lead to false negatives, through differing levels of response. For example, while NAC may destroy the metastases in the SLN, residual foci may remain in the non-SLNs.…”
Section: Timing Of Sln: Before or After Neoadjuvant Chemotherapymentioning
confidence: 99%